On the stability of morphology and performance of neural interfacing electrodes fabricated via CO2-snow-assisted hierarchical surface restructuring - Alexander Blagojevic; Wesley Seche; Pouya Tavousi; Sina Shahbazmohamadi; Shahram Amini (PLoS ONE, 2026)
Long-term implantable neural interfacing devices play a critical role in treating various neurological disorders, with their functionality largely dependent on the performance of electrodes and microelectrode arrays. Femtosecond laser Hierarchical Surface Restructuring (HSR™) is an advanced surface treatment technology that significantly enhances a platinum-10% iridium (Pt-10Ir) electrode’s electrochemical performance, improving energy efficiency, specificity, and signal-to-noise ratio. Additionally, HSR™ facilitates electrode miniaturization, allowing them to be manufactured smaller, for a less invasive profile. Electrode surfaces produced via HSR™ technology contain multiscale structures, including nanoscale features that, while contributing to superior performance, are sometimes weakly bonded and may detach due to mechanical agitation during testing or implantation. This detachment could lead to a high initial performance, that may gradually decline during prolonged use. Preemptively removing these nanostructures stabilizes the electrode surface, enhancing the stability of its morphology and potentially electrochemical performance. This study introduces a novel, in-operando, CO₂-snow-assisted HSR™ process and benchmarks it against other prevalent surface cleaning methods post-fabrication, such as ultrasonic cleaning, on improving electrode stability and performance. Both qualitative and quantitative analyses indicate that all cleaning methods enhance electrode stability. However, ultrasonic cleaning was found to be more destructive compared to CO₂-snow-assisted HSR™ processing, resulting in reduced electrochemical performance. In contrast, in-operando CO₂-snow-assisted processing provided similar or superior improvements in surface stability, while preserving higher electrochemical performance in vitro and enabling a faster processing time. This study is the gateway to further assess the stability in vivo , which is the intended next step of the research.